Improving serrated adenoma detection rate in the colon by electronic chromoendoscopy and distal attachment: systematic review and meta-analysis - Aziz, Muhammad; Desai, Madhav; Hassan, Seemeen; Fatima, Rawish; Dasari, Chandra S.; Chandrasekar, Viveksandeep Thoguluva; Jegadeesan, Ramprasad; Duvvuri, Abhiram; Patel, Harsh; Rai, Tarun; Sathyamurthy, Anjana; Kohli, Divyanshoo R.; et al. (Gastrointestinal endoscopy, 2019)
The evidence for modification of conventional colonoscopy using either “distal attachments” (DAs; endocap, endocuff, and endoring) or “electronic chromoendoscopy” (EC; narrow-band imaging [NBI], iScan, blue-light imaging, autofluorescence imaging, and linked-color imaging) to improve the detection of serrated adenomas during colonoscopy has shown conflicting results. A comprehensive literature search was performed using Medline, Google Scholar, Embase, and Cochrane Library based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Randomized controlled trials (RCTs) comparing any DA or EC with high-definition white-light colonoscopy for detection of serrated adenomas (sessile serrated adenoma/polyp and traditional serrated adenoma) were included. The primary outcome was serrated adenoma detection rate (SADR) defined as the number of patients with at least 1 serrated adenoma of total patients in that group. The secondary outcome was the number of serrated adenomas per subject. Pooled rates were reported using risk ratio (RR) with 95% confidence interval. Seventeen studies with 13,631 patients (56% men; age range, 50-66 years) met the inclusion criteria. The use of DAs (RR, 1.21; P = .45) and EC (RR, 1.29; P = .09) during colonoscopy did not show a significant improvement in SADR. The SADR using EC was 6.9% (4 studies) and that with NBI alone was 3.7% (3 studies). The results indicate that, except for NBI, the use of DAs or EC during colonoscopy does not improve detection of serrated adenomas in the colon. More RCTs evaluating NBI are needed to explore the effect.